Numerical technique for wireless communication system with high speed movement - Shafrida, Sahrani; Kuroda, Michiko (Institute of Electrical and Electronics Engineers Inc., 2016)
Numerical technique for the analysis of EM field with high speed moving dielectric body by using FDTD method with Overset Grid Generation method considering Lorentz transformation is presented. The characteristic of EM field when incident wave hits the moving dielectric body with high velocity value are analyzed. The accuracy of the proposed technique is validated. Good agreements are obtained between numerical results and theoretical results. The development of this numerical technique will give a great impact for many areas, particularly for the future high speed mobile communication systems used in transportation and aerial radar systems to detect the high speed motion of a moving boundary